2023
DOI: 10.3390/plants12162922
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Carbon Nanodots and Manganese Ferrite (MnFe2O4) Nanoparticles in Stimulating Growth and Antioxidant Activity in Drought-Stressed Maize Inbred Lines

Abstract: Despite being the third most-consumed crop, maize (Zea mays L.) is highly vulnerable to drought stress. The predominant secondary metabolite in plants is phenolic acids, which scavenge reactive oxygen species to minimize oxidative stress under drought stress. Herein, the effect of carbon nanodots (CND) and manganese ferrite (MnFe2O4) nanoparticles (NP) on the drought stress tolerance of maize has been studied. The experimental results revealed that the highest leaf blade length (54.0 cm) and width (3.9 cm), ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…The results from seven physiochemical traits studied in 41 maize-inbred lines under drought stress are exhibited in Table S1 . These data have been studied previously by Ilyas et al (2023) [ 31 ]. The caffeic acid content ranged from 0.000 to 2.915 µg/mL across the 41 maize-inbred lines, with a mean value of 1.295 µg/mL.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The results from seven physiochemical traits studied in 41 maize-inbred lines under drought stress are exhibited in Table S1 . These data have been studied previously by Ilyas et al (2023) [ 31 ]. The caffeic acid content ranged from 0.000 to 2.915 µg/mL across the 41 maize-inbred lines, with a mean value of 1.295 µg/mL.…”
Section: Resultsmentioning
confidence: 86%
“…Group II comprised 12 accessions representing 32.4% of the population, and the admixed group included 5 accessions [29]. Likewise, Sa et al (2023) [30] investigated the population structure of 80 maize-inbred lines using STRUCTURE 2.3 software. They revealed that all the inbred lines were divided into two primary groups (Group I and Group II) and one admixed group.…”
Section: Discussionmentioning
confidence: 99%
“…MnFe 2 O 4 NPs have been shown to mitigate the effects of drought stress in maize. Thus, treatment with NPs stimulated shoot length and biomass and chlorophyll content . In a field experiment, spraying the leaves of soybean ( Glycine max L.) with Mn nanochelate showed an increase in plant resistance to drought, which was manifested in stimulation of biometric parameters and yield compared to plants not treated with nanochelate .…”
Section: Effect Of Manganese Nanoparticles On Plantsmentioning
confidence: 99%
“…Thus, treatment with NPs stimulated shoot length and biomass and chlorophyll content. 118 In a field experiment, spraying the leaves of soybean (Glycine max L.) with Mn nanochelate showed an increase in plant resistance to drought, which was manifested in stimulation of biometric parameters and yield compared to plants not treated with nanochelate. 119 An increase in drought resistance under the influence of Mn 3 O 4 NPs was shown for corn Zea mays L. Stimulation of biometric parameters, stimulation of cell mitosis, an increase in total protein content, as well as a decrease in H 2 O 2 and MDA levels were noted.…”
Section: Effect On Plant Resistance To Abiotic Stressesmentioning
confidence: 99%
See 1 more Smart Citation